2013
DOI: 10.5455/2319-2003.ijbcp20130818
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative identification of the active principles in Citrullus colocynthis and evaluation of its teratogenic effects in albino rats

Abstract: Background: This study was designed to identify the active contents of Citrullus colocynthis plant and to examine their teratogenicity in rats. The fruit pulp of the poisonous plant was collected randomly from Suq-Alkhamis district, Tripoli, Libya. Methods: The glucoside colocynthin was isolated by lead acetate method while the alkaloids and saponins were isolated by maceration method. These active principles were then identified by chemical tests, color reactions and thin layer chromatography. Possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Alkaloids 0.025 g of crude extracts were dissolved in 20 mL of 5% hydrochloric acid (HCl) and sonicated to improve solubitity. The mixture was used to determine with the following test; 38…”
Section: Phytochemical Screening Of the Extractsmentioning
confidence: 99%
“…Alkaloids 0.025 g of crude extracts were dissolved in 20 mL of 5% hydrochloric acid (HCl) and sonicated to improve solubitity. The mixture was used to determine with the following test; 38…”
Section: Phytochemical Screening Of the Extractsmentioning
confidence: 99%
“…The study displayed treatogenic effects, when gross anatomical observation is done on the 20th day of gestation it revealed a high percentage of resorbed fetuses, smaller size and weight fetuses as well as absence of coccygeal vertebrae, metacarpal and metatarsal bones, and carpal and tarsal bones. (75).…”
Section: Toxicitymentioning
confidence: 99%
“…In addition, moderate to severe hypotension, moderate hypoglycemic, and hepatic injury with increasing of hepatic enzymes were recorded in a case of acute C. colocynthis toxicity (Table 2). Moreover, the extract of fruit pulp of C. colocynthis was reported to cause teratogenic effects if given during the early stage of pregnancy in rats [121]. Studying the effects of 100 or 200 mg/kg/day of either pulp or seed extracts of C. colocynthis on male rabbits, for one month, indicated that 200 mg/kg/day of pulp extract was fatal for all animals and 50% of animals treated with pulp extract at 100 mg/kg/day did not survive to the end of the study.…”
Section: Sansevieria Trifasciata Prainmentioning
confidence: 99%